Cerebello-cerebral network dynamic of basketball athletes in motor control tasks - Qi, Y.; Wang, Y.; Fang, W.; Li, X.; Du, X. (Medicine & Science in Sports & Exercise, 2026)
Abstract Purpose: The cerebellum is essential for motor control due to its dynamic interactions with the sensorimotor network (SMN). Within the cerebellum, motor functions are organized into two distinct representations, known as the first motor representation (MRP1) and the second motor representation (MRP2). While long-term training in athletes optimizes motor control, the functional reorganization in the cerebellum and its interaction with the SMN remains unclear. Specifically, the unique contributions of MRP1 and MRP2 to motor expertise remain poorly understood.